Structure and corrosion resistance of vacuum-arc multi-period CrN/Cu, ZrN/Cu, and NbN/Cu coatings - Postelnyk, H.O.; Sobol, O.V.; Stolbovoy, V.A.; Serdiuk, I.V.; Chocholaty, O. (Вопросы атомной науки и техники, 2020)
The structure and properties of vacuum-arc multi-period composite coatings of the MeN/Cu system (where Me is Cr, Zr, and Nb) are studied. It was found that at the smallest nanolayer thickness (about 8…10 nm) of composites in the layers of all systems, only a phase with an fcc lattice is formed, without a pronounced texture in the nitride layers. For ZrN and CrN, the phases with an fcc lattice are equilibrium, and for NbN, they are nonequilibrium. An increase in the thickness of nitride layers leads to the appearance of a texture in ZrN/Cu and CrN/Cu systems and the formation of an equilibrium ε-NbN phase in the layers of the NbN/Cu system. Tests for corrosion resistance in the environment of the formation of chloride ions showed that the coatings are anodic reaction. The best corrosion properties were obtained for coatings with the smallest layer thickness (about 8…10 nm). Проведено дослідження структури і властивостей вакуумно-дугових багатоперіодних композиційних покриттів системи MeN/Cu (де Me – Cr, Zr і Nb). Встановлено, що при найменшій товщині наношарів (близько 8…10 нм) композитів у шарах всіх систем формується тільки фаза з ГЦК-решіткою, без помітно вираженої текстури в нітридних шарах. Для ZrN і CrN фази з ГЦК-решітками є рівноважними, а для NbN – нерівноважними. Збільшення товщини нітридних шарів призводить до появи текстури в ZrN/Cu- та CrN/Cuсистемах і формування рівноважної ε-NbN-фази в шарах системи NbN/Cu. Випробування на корозійну стійкість у середовищі утворення хлорид-іонів показали, що покриття мають анодний характер. Найкращі корозійні властивості були отримані для покриттів з найменшою товщиною шарів (близько 8…10 нм). Проведено исследование структуры и свойств вакуумно-дуговых многопериодных композиционных покрытий системы MeN/Cu (где Me – Cr, Zr и Nb). Установлено, что при наименьшей толщине нанослоев (около 8…10 нм) композитов в слоях всех систем формируется только фаза с ГЦК-решеткой, без явно выраженной текстуры в нитридных слоях. Для ZrN и CrN фазы с ГЦК-решеткой являются равновесными, а для NbN – неравновесными. Увеличение толщины нитридных слоев приводит к появлению текстуры в ZrN/Cu- и CrN/Cu-системах и формированию равновесной ε-NbN-фазы в слоях системы NbN/Cu. Испытания на коррозионную стойкость в среде образования хлорид-ионов показали, что покрытия имеют анодный характер. Наилучшие коррозионные свойства были получены для покрытий с наименьшей толщиной слоев (около 8…10 нм).